The Use of Social Media as An English Learning Resource for The Students of Islamic University of Kadiri Kediri - Adry Nurdina Fajriah; Irwan Sulistyanto; Wawan Herry Setyawan (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
The aim of this research was to describe the kinds of social media that are mostly used and how students use social media as English learning resources. This research used a quantitative descriptive method with the data collection technique of a survey and simple random sampling technique. The subjects of research were all semesters in class A, Faculty of English Education, students of the Islamic University of Kadiri Kediri. The result of statistical calculations showed that YouTube was the social media platform that students used the most frequently as a resource for learning English, with 91.9% of students admitting to utilizing the platform to get better at listening. Next, according to 81.8% of students, they utilized YouTube to hone their speaking abilities. Additionally, 79.8% of students claimed to have used YouTube to advance their reading comprehension, and 77.8% claimed to have used it to advance their English writing abilities. The majority of students (37.97%) in the English Education faculty chose watching English videos as a resource for learning the language. Then, 32.49% of students said that an effective way to study English was to follow an English learning account. Furthermore, 29.54% of students claimed that speaking with native speakers in person was a useful way to learn English. Based on this research, it can be stated that the research that has been carried out has obtained positive results in accordance with existing theory and has benefits for the faculty, students, readers, and future researchers to increase insight in choosing the use of social media that can be used as an English learning resource. Thus, it can be concluded that social media YouTube can be a useful and effective tool for students to learn English.